Traffic Engineering based on Shortest Path routing algorithms for FTV (Free-Viewpoint Television) applications - Solis, Priscila; Domingues Garcia, Henrique (NCA : 2016 IEEE 15th International Symposium on Network Computing and Applications : October 31, 2016-November 2, 2016, 2016)
This paper proposes a traffic engineering methodology based on the self-similarity parameter of video traffic as a restriction on an Integer Linear Programming problem (ILP) for the definition of link costs for routing optimization in the OSPF (Open Shortest Path First ) routing protocol. The goal is to optimize video routing considering QoS constraints and to identify the maximum delay and link load parameters for transmission between video sources and middleboxes for FTV (Free Viewpoint Television) applications. The proposal was evaluated in a simulation environment and the results show that the routing optimization procedure based on the self-similar parameter of video traffic for defining link weights, can significantly reduce the delay in the network and allow the identification of more accurate threshold values for link loads and delays for video transmission on the Internet.